Release performance and sustained-release efficacy of emamectin benzoate-loaded polylactic acid microspheres - Ming-ming YIN; Xin-yan ZHU; Fu-liang CHEN (Journal of Integrative Agriculture, 2018)
High-performance liquid chromatography (HPLC) was employed to determine drug release rates based on emamectin benzoate concentrations in the medium. Release kinetics equations were used to fit the drug release behavior. The effects of particle size and release medium pH on the release rate were also investigated. The indoor toxicity of emamectin benzoate-loaded polylactic acid microspheres on the diamondback moth larva (Plutella xylostella) was studied to explore drug sustained-release performance. In acidic and neutral media, the drug release behavior of the microspheres was in accord with the first-order kinetics equation. Increasing the spray dosage of emamectin benzoate-loaded polylactic acid microspheres initially resulted in an equivalent insecticidal efficacy with the conventional emamectin benzoate microemulsion. However, the drug persistence period was four-fold longer than that observed using the conventional formulation. The developed emamectin benzoate-loaded polylactic acid microspheres showed dramatic sustained-release performance. A treatment threshold of greater than 35 mg mL−1 was established for an efficient accumulated release concentration of emamectin benzoate-loaded microspheres.